2011
DOI: 10.1088/0022-3727/44/21/215302
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced atomic diffusion at the interface between release agent coating and mould substrate in a glass moulding press

Abstract: In a glass moulding press (GMP) for refractive/diffractive hybrid lenses, to improve the service life of nickel-phosphorus (Ni-P) plated moulds, it is necessary to control the diffusion of constituent elements from the mould into the release agent coating. In this study, diffusion phenomena of constituents of NiP plating are investigated for two types of release agent coatings, iridium-platinum (Ir-Pt) and iridium-rhenium (Ir-Re), by cross-sectional observation, compositional analysis and stress measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Since EBSD and XRD measurements revealed average grain sizes of 70-90 nm and crystallite sizes of 20-30 nm, grain boundary diffusion is the most probable diffusion mechanism. This is supported by the diffusion analysis of Ni thin films in [8]. After sputtering by 20 nm, nickel oxide is removed and only metallic nickel is detected to be present in the PtIr layer, in agreement with external selective oxidation.…”
Section: Resultssupporting
confidence: 64%
“…Since EBSD and XRD measurements revealed average grain sizes of 70-90 nm and crystallite sizes of 20-30 nm, grain boundary diffusion is the most probable diffusion mechanism. This is supported by the diffusion analysis of Ni thin films in [8]. After sputtering by 20 nm, nickel oxide is removed and only metallic nickel is detected to be present in the PtIr layer, in agreement with external selective oxidation.…”
Section: Resultssupporting
confidence: 64%
“…Thus, coating is often used for extending mold life and thereby leading to the cost reduction of the molded optical products. There are mainly three types of coatings available in the market, namely, ceramic coating (TiAlN, CrN, TiBCN or TiBC) [63], noble metal coating (Pt/Ir [64,65] and Re/Ir [66,67]), and carbon coating (diamondlike coating, amorphous carbon coating) [68]. Ceramic coatings have been widely used in making machining tools, and therefore are straightforward to apply to PGM molds.…”
Section: Mold Materialsmentioning
confidence: 99%
“…Noble metal coatings, especially the Pt/Ir alloy coating, can avoid such adhesion [64,65]. Nevertheless, it has been found that the Pt/Ir layer is not stable [66,67], and that the substrate material can diffuse into the coating layer and reduce its quality. However, the noble metal coating of Re/Ir demonstrates very stable properties [66] and low wetting angle among various coating materials [67].…”
Section: Mold Materialsmentioning
confidence: 99%
See 2 more Smart Citations